Kluyvera mediastinitis following open-heart surgery: a case report. - Sierra-Madero, J (1990)
Reports of serious infections caused by Kluyvera spp. have been rare. A case of Kluyvera sp. mediastinitis and bacteremia in a man after open-heart surgery is described. The clinical significance of Kluyvera sp. isolates was debated in early descriptions of the organism. More recent reports, as well as the present case, suggest that the pathogenic potential of this organism is being increasingly recognized by clinicians and microbiologists.